Organizational culture and ambidexterity in the entrepreneurial orientation-performance link in Indonesia's police - Thamrin, Muhammad; Susanto, Perengki; Syahrizal, Syahrizal (International Journal of Innovative Research and Scientific Studies, 2025)
This study examines how Entrepreneurial Orientation (EO), encompassing innovativeness, proactiveness, and risk-taking, impacts the organizational performance of sector police units in Indonesia. Although EO has been widely examined in the business sector, its application within public sector institutions, particularly in police organizations in developing countries, remains underexplored. To address this gap, the study further examines whether organizational culture and organizational ambidexterity moderate the relationship between entrepreneurial orientation (EO) and performance. Using a quantitative approach, data were collected through an electronic survey from 328 strategically selected personnel across 214 sector police units, chosen through purposive sampling. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate the causal relationships among variables. The results reveal that risk-taking (β = 0.253), proactiveness (β = 0.227), and innovativeness (β = 0.182) each significantly contribute to improved organizational performance. Organizational culture positively moderates the effect of innovativeness (β = 0.196) but negatively moderates the relationship between proactiveness and performance (β = -0.233), while showing no significant moderation for risk-taking. Organizational ambidexterity significantly strengthens the effect of proactiveness (β = 0.173) but does not moderate the other relationships. These findings contribute to Institutional Theory and the Resource-Based View (RBV) by demonstrating how internal organizational factors shape the influence of EO in a public sector context.